Delayed Closure of Giant Omphaloceles in West Africa: Report of Five Cases - Oumama El Ezzi; Raymond Bossou; Olivier Reinberg; Sabine Vasseur Maurer; Anthony de Buys Roessingh (Georg Thieme Verlag KG, 2017)
Giant omphalocele (GO) management is controversial and not easy. Conservative management at birth and delayed surgical closure is usually mandatory. Postponed surgery may be challenging and carry the risk of intensive care treatment. We report on five children who were treated in our department for GO between 2000 and 2010. Initially, the patients were managed conservatively in West Africa. Delayed closure of the ventral hernia was performed in Switzerland after patient transfer through a nongovernmental organization. Fascial closure was performed at the median age of 23 months. Median diameter of the hernias was 10 × 10 cm ranging from 10 × 8 cm to 24 × 15 cm. Four (80%) patients had associated anomalies. Three children needed mechanical ventilation in the intensive care unit after surgery. Median hospitalization was 19 days. Complications were seen in two patients. The follow-up showed no recurrence of ventral hernia. There was no mortality. This report shows that conservative management of a GO at birth with delayed closure of the ventral hernia after transferring the patients to a European center is a safe approach for West African children and avoids life-threatening procedures. Delayed closure of a GO may be nevertheless challenging everywhere.